Spiking Patterns of Neocortical L5 Pyramidal Neurons in Vitro Change with Temperature - Hedrick, Tristan; Waters, Jack (Frontiers in Cellular Neuroscience, 2011)
A subset of pyramidal neurons in layer 5 of the mammalian neocortex can fire action potentials in brief, high-frequency bursts while others fire spikes at regularly-spaced intervals. Here we show that individual layer 5 pyramidal neurons in acute slices from mouse primary motor cortex can adopt both regular and burst spiking patterns. During constant current injection at the soma, neurons displayed a regular firing pattern at 36-37 °C, but switched to burst spiking patterns upon cooling the slice to 24-26 °C. This change in firing pattern was reversible and repeatable and was independent of the somatic resting membrane potential. Hence these spiking patterns are not inherent to discrete populations of pyramidal neurons and are more interchangeable than previously thought. Burst spiking in these neurons is the result of electrical interactions between the soma and distal apical dendritic tree. Presumably the interactions between soma and distal dendrite are temperature-sensitive, suggesting that the manner in which layer 5 pyramidal neurons translate synaptic input into an output spiking pattern is fundamentally altered at sub-physiological temperatures.